2014
DOI: 10.1097/prs.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Survival of Pedicled Abdominal Flaps in a Rat Model after Perivascular Application of Botulinum Toxin Type A

Abstract: The presence of botulinum toxin type A in the postsurgical flap microenvironment augments tissue perfusion and its inflammatory response and, ultimately, survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…Kim et al (2) proposed a sympatholytic mechanism for BTX-A, and reported an increased survival of random flaps in rats using BTX-A by 8.3%. Arnold et al (10) proposed that BTX-A improves flap survival on account of its antiinflammatory and vasoactive effects.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2) proposed a sympatholytic mechanism for BTX-A, and reported an increased survival of random flaps in rats using BTX-A by 8.3%. Arnold et al (10) proposed that BTX-A improves flap survival on account of its antiinflammatory and vasoactive effects.…”
Section: Discussionmentioning
confidence: 99%
“…1,6-8, 10, 22, 32, 36, 39, 40, 49, 50, 54, 57,62 In these studies, a rat model was most commonly used (n = 14/15) and there was significant variability in BTX dose (0.1-20 IU), application method (subdermal, intradermal, subcutaneous, intramuscular or perivascular injection, direct application to the vessels, or tissue bath), treated flaps (random cutaneous, abdominal or dorsal cutaneous, transverse rectus abdominis myocutaneous, cremaster, spinotrapezius, or gastrocnemius muscular), and evaluation time points (5 minutes to 21 days). Better flap survival rates, 10,22,32,36,39,50,54,57 increased angiogenesis and angiogenic marker expression, 36,39,40,49,50,54 improved blood flow, 54,57 vasodilation, 8,39,50,62 and reduced inflammation and inflammatory marker expression 1,6 were observed in the BTX treatment groups as compared to controls. Interestingly, BTX-A also improved random cutaneous flap survival in rats after short-and long-term tobacco exposure, demonstrating its potential efficacy for the prevention of reconstructive and revascularization surgery complications in smokers.…”
Section: Btx-a Utility In Vasospasm Prevention: Relevant Animal Studiesmentioning
confidence: 91%
“…49,57 In these and numerous other animal studies, improved flap survival, increased tissue perfusion, vasodilation, and angiogenesis after BTX-A pretreatment has been demonstrated. 6,8,39,49,57,66 Hence, the reported upregulation of Rho kinase expression in response to BTX-A seems to be contradictory to its well-reported vasodilatory effects in animal models and Raynaud's phenomenon treatments in humans. 20,46,64 Accordingly, Schweizer et al hypothesized that increased RhoA immunoexpression after BTX-A administration could result from a compensatory overexpression in response to functional inhibition, 57 however, no targeted investigations of BTX A-specific effects on RhoA downstream effectors in the ROCK pathway have been reported.…”
Section: Figmentioning
confidence: 95%
“…In another study, it increased skin‐flap viability in diabetic rats, which was associated with an increase of lumen diameter, external arterial diameter and lumen/wall thickness ratio . At the molecular level, BoNT/A affected the expression of vascular endothelial growth factor, platelet endothelial cell adhesion molecule 1, CD31, CD34, interleukin (IL)‐1 and tumour necrosis factor‐α in cutaneous flaps . BoNT/A reduced the hypoxic area and the number of oxidative stress‐associated DNA‐damaged cells and apoptotic cells in the cutaneous ischaemia–reperfusion injury sites .…”
Section: Experimental Studies Of Cutaneous Effects Of Botulinum Neuromentioning
confidence: 99%